Hak Cipta Karya Seni Lukis sebagai Jaminan Fidusia - Ni Kadek Emy Kencana Wati; I Nyoman Putu Budiartha; I Ketut Sukadana (Warmadewa Press, 2021)
The use of copyright for painting artworks in the Intellectual Property Law system in Indonesia provides many benefits for painters as copyright owners or copyright holders. A creator or copyright holder has Economic Rights on his work which includes the right to duplicate, display, and lease his work to third parties. Copyright Law No. 28/2014 states that copyright can be used as an object of Fiduciary security. This study aims to determine the characteristics of the copyright of painting works that can be used as fiduciary guarantees to get credit in banking and to analyze the execution of copyright guarantees of painting works if the debtor defaults The method used is normative legal research with a statutory approach and a conceptual approach, and the sources of legal materials used are primary and secondary legal materials with literature collection techniques which are analyzed in descriptive analytical form. Based on the results of the study, it can be concluded that the characteristics of copyright in painting are providing protection for works of art and providing economic rights for the creators or copyright holders and moral rights for the creators. The execution of copyright guarantees can be done by executorial method in accordance with article 29 of the Fiduciary Law.